The role of context and relevance in translating European Union texts - Ilona Lekhner; Lechner Ilona; Huszti Ilona; Лехнер Ілона; Густі Ілона (Видавничий центр КНЛУ, 2021)
Abstract. The article presents the nature and legitimacy of translation studies; it examines the function of a translator, its role during the translation process and the generated linguistic product from the point of view of cognitive pragmatics. In the present study we are looking for the answer to what factors influence the translator in his/her activity, what aspects he/she keeps in mind, how relevance theory prevails in translation, what role the current context, target audience and readers’ prior knowledge have in interpreting the translated text. In order to answer the questions, in the first part we summarize the opinions published in the literature, then we examine our hypothesis with the method of structural discourse analysis in relation to three languages (English, German, Hungarian) in EU texts, according to which, despite the European Union’s language policy aspirations, similarities and differences can be noticed depending on what the translator considered relevant to highlight. In the examined texts we can find formal, semantic and pragmatic differences according to the levels of identity. In the course of the analysis, we have made an attempt to highlight the semantic and pragmatic similarities and the differences between the versions, the factors which may cause them, and also their connection with the cognitive context, relevance and the general context. As a first step, we identified the different parts of the texts, and then the reason for the differences was revealed during the analysis. The aim is therefore to support our hypothesis and to illustrate with linguistic examples that context and relevance are central to translation.

Резюме. У статті представлено діяльність перекладача з погляду когнітивної прагматики, досліджено його роль у процесі перекладу, з’ясовано відповідність створеного мовного продукту з погляду релевантності. Описано фактори, що впливають на діяльність перекладача; указано на аспекти, які перекладач уважає пріоритетними; продемонстровано, як реалізовується теорія релевантності в процесі перекладу, яку роль відіграє контекст, цільова аудиторія та попередні знання читачів при інтерпретації перекладеного тексту. У першій частині статті узагальнено результати попередніх досліджень; проаналізовано тексти про Європейський Союз методом структурного аналізу дискурсу, перекладені трьома мовами (англійською, німецькою та угорською); доведено, що в тексті перекладу спостерігаються деякі відмінності з погляду релевантності у зв’язку з наміром перекладача передати найважливіший зміст тексту-оригіналу. У досліджених текстах відповідно до рівнів ідентичності виявлено формальні, семантичні та прагматичні відмінності. У другій частині статті зосереджено увагу насамперед на аналізі семантичних і прагматичних спільних і відмінних рис текстів; встановлено, які фактори лежать в основі подібностей і відмінностей, як вони пов’язані з поняттями когнітивна сфера перекладача і цільової аудиторії, релевантність і контекст. Визначено відмінності при перекладі, а відтак указано на можливі причини їх виникнення. На конкретних прикладах підтверджено, що контекст і релевантність є основними чинниками у процесі перекладу.
Роль контексту та релевантності в процесі перекладу текстів Європейського Союзу
Keywords: translation studies; pragmatics; cognitive context; relevance theory; context; перекладознавство; прагматика; когнітивна сфера; теорія релевантності; контекст